Residential area and screening venue location features associated with spatial variation in breast cancer screening invitation response rates: an observational study in Greater Sydney, Australia. Issue 4 (15th April 2021) - Khan, Jahidur Rahman; Carroll, Suzanne Jane; Warner-Smith, Matthew; Roder, David; Daniel, Mark
Abstract : Objectives: Participation in breast cancer screening (BCS) varies at the small-area level, which may reflect environmental influences. This study assessed small-area variation in BCS invitation response rates (IRRs) and associations between small-area BCS IRR, sociodemographic factors, BCS venue distance and venue location features in Greater Sydney, Australia. Methods: BCS IRR data for 2011–2012 were compiled for 9528 Australian Bureau of Statistics Statistical Area Level 1 (SA1) units (n=227 474 women). A geographial information system was used to extract SA1-level sociodemographic features (proportions of women speaking English at home, full-time employed and university educated, and proportion of dwellings with motor vehicles), SA1-level distance to closest venue(s) (expressed as quartiles), and closest venue(s) colocated with bus stops, train station, hospital, general practitioner and shops. Associations between area-level features, BCS venue distance, venue location features and IRR were estimated using ordinary least square-type spatial lag models including area education as a covariate. Results: BCS IRR varied across SA1s (mean=59.8%, range: 0%–100%), with notable spatial autocorrelation (Moran's I=0.803). BCS IRR was positively associated with greater SA1-level proportion of women speaking English at home (β=2.283, 95% CI 2.024 to 2.543), women's education (in the model including speaking English at home β=0.454, 95% CI 0.211 to 0.697), dwellings with motor vehicles (β=1.836, 95% CI 1.594 to 2.078), greater distance to venue (eg, most distant quartile compared with closest: β=6.249, 95% CI 5.489 to 7.008), and BCS venue colocated with shops (β=0.762, 95% CI 0.273 to 1.251). Greater SA1-level women employment (β=−0.613, 95% CI −0.898 to −0.328) and venue colocated with train station (β=−1.889, 95% CI −2.376 to −1.402) or hospital (β=−0.677, 95% CI −1.164 to −0.189) were inversely related to BCS IRR. Conclusions: Small-area variation in BCS IRR exists for Greater Sydney and is strongly related to sociodemographic factors that, together with BCS venue location features, could inform targeted attempts to improve IRR.